1978
DOI: 10.1007/bf00501376
|View full text |Cite
|
Sign up to set email alerts
|

Lungs as a generator of prostacyclin — Hypothesis on physiological significance

Abstract: In vivo anti-platelet de-aggregatory activity of exogenous prostacyclin is enhanced after its passage through the pulmonary circulation of anaesthetized cats, probably because of a concomitant generation of endogenous prostacyclin by the lungs. Evidence is also presented that perfused lungs of guinea pigs and rats spontaneously release considerable amounts of prostacyclin. It is therefore postulated that a continuous biosynthesis of prostacyclin by pulmonary endothelium is a general physiological phenomenon, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…The present results are in agreement with in vitro studies with the aggregometer in whch PGI2 was a potent inhibitor of platelet aggregation Gryglewski et al, 1976;Lefer et aL, 1978). It has been reported recently that isolated perfused lungs of rats and guinea pigs and the lungs of anesthetized cats spontaneously release a "PGI2-like" substance (Gryglewski et aL, 1978). If the lungs release "PGl2-like" substances and these factors are formed by endothelial cells in upstream vessels, it is possible that these substances serve to inhibit platelet aggregation and thrombus formation in the lung and to maintain the pulmonary vascular bed in a dilated state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are in agreement with in vitro studies with the aggregometer in whch PGI2 was a potent inhibitor of platelet aggregation Gryglewski et al, 1976;Lefer et aL, 1978). It has been reported recently that isolated perfused lungs of rats and guinea pigs and the lungs of anesthetized cats spontaneously release a "PGI2-like" substance (Gryglewski et aL, 1978). If the lungs release "PGl2-like" substances and these factors are formed by endothelial cells in upstream vessels, it is possible that these substances serve to inhibit platelet aggregation and thrombus formation in the lung and to maintain the pulmonary vascular bed in a dilated state.…”
Section: Discussionsupporting
confidence: 92%
“…Prostacyclin decreases systemic arterial pressure in all species in which it has been studied, and a PGI 2 analog has been shown to have marked vasodilator activity in the feline pulmonary lobar and mesenteric vascular beds Paustian et al, 1977;Armstrong et al, 1978;Fitzpatrick et al, 1978;Lefer et al, 1978). Although PGI 2 is formed in blood vessels, "PGl2-like" substances are released from the lung, and the metabolite, 6-keto-PGFi a , is released from the lung after immunological challenge, the direct effects of PGI 2 on the pulmonary vascular bed are uncertain (Dawson et al, 1976;Gryglewski et aL, 1976;Gryglewski et al, 1978). In a recent study in the anesthetized dog, PGI 2 , in a dose of 0.5 fig/kg, iv, caused a 1.4% decrease in pulmonary arterial pressure (Fitzpatrick et al, 1978).…”
mentioning
confidence: 99%
“…We have, therefore, suggested that under resting conditions, the pulmonary vascular bed is maintained in a dilated state by production of a vasodilator product in the cyclooxygenase pathway (28). Recent evidence suggests that this vasodilator product in the cyclooxygenase pathway is a PGI2-like substance (6,23,24). It would therefore be of interest to ascertain if industrial pollutants such as NO2 or S02 have adverse effects on enzymes such as cyclooxygenase or prostacyclin synthetase which function to synthesize PGI2 which serves to maintain the pulmonary vascular bed in a dilated state under resting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The endoperoxide intermediates (PGG2 and PGH2) are then converted by terminal enzymes into primary prostaglandins (PG), thromboxane A2 (TXA2) or prostacyclin, PG12 (2)(3)(4)(5)(6)(7)(8)(9). The distribution and activity of terminal enzymes determine the pattern of products formed from endoperoxide intermediates in an organ (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperventilation is known to lead to the release of prostacyclin from the lungs (16)(17)(18). PGI2, in turn, is a potent pulmonary vasodilator of fetal and newborn lung (6, 7, 9).…”
Section: Control Tcpmentioning
confidence: 99%